Plant pathogenic fungus F. solani mediated biosynthesis of nanoceria: antibacterial and antibiofilm activity. Issue 48 (29th April 2016) - Venkatesh, K. S.; Gopinath, K.; Palani, N. S.; Arumugam, A.; Jose, Sujin P.; Bahadur, S. Asath; Ilangovan, R.
Abstract : The present study reports the synthesis of CeO2 nanoparticles using Fusarium solani . The biosynthesized CeO2 nanoparticles were subjected to different characterization techniques and also showed potential antibacterial and antibiofilm activities. Abstract : The aim of the present study was to synthesize CeO2 nanoparticles using plant pathogenic fungus F. solani and also to study the antibacterial activity as well as the influence on the inhibition of biofilm formation against biomedically important bacterial strains namely Staphylococcus aureus, Psedomonas aeriginosa, Escherichia coli and Klebsiella pneumoniae . Thermogravimetric/differential thermal analysis (TG/DTA) suggested a crystallization temperature of the as-synthesized CeO2 nanopowder at 400 °C. Powder X-ray diffraction analysis and Raman spectroscopy substantiated the presence of CeO2 nanoparticles with a cubic fluorite structure. The contribution of functional groups corresponding to the F. solani fungal supernatant for the synthesis of CeO2 nanoparticles was studied by Fourier transform infrared (FTIR) spectroscopy. The room temperature photoluminescence spectrum of calcined CeO2 nanopowder was recorded. Field emission scanning electron microscopy (FESEM) equipped with energy dispersive X-ray spectroscopy (EDAX) ascertained the formation of homogeneously distributed spherically shaped CeO2 nanoparticles. Furthermore, transmission electron microscopy (TEM) demonstrated the spherical morphology of the CeO2 nanoparticles having sizes ranging from 20 to 30 nm and also the selected area electron diffraction (SAED) pattern revealed the polycrystalline nature of the CeO2 nanoparticles, which is consistent with the XRD results. The presence of surface oxidation states Ce (3d) and O (1s) of the CeO2 nanoparticles was confirmed by X-ray Phoelectron Spectroscopy (XPS) analysis. The antibacterial activity of CeO2 nanoparticles was evaluated by the disc diffusion method and it showed the highest activity against P. aeruginosa as well as K. pneumoniae . In addition, the inhibition on biofilm formation by CeO2 nanoparticles has also been examined by confocal laser scanning microscopy (CLSM). Furthermore, the electrochemical property of the biosynthesized CeO2 nanoparticles was studied by the cyclic voltammetry technique.